An Empirical Study on the Use Intention of Electronic Cash Collection System in Nigerian Federal Hospitals - Kabir, Muhammad Auwal; Abba, Magaji; Abubakar, Abdulkadir (International Journal of Emerging Trends in Social Sciences, 2018)
It is a well-known fact that the use of electronic systems around the globe has facilitated and enhanced the efficiency in organizations. In light of this, federal hospitals in Nigeria have started using electronic collection system for cash collection purposes. Electronic cash collection system (e-collection) is a computerized system designed to handle cash collections with a view to block revenue leakages that are widespread within the Nigerian public sector organizations. However, the continuous use of the system is being faced with great resistance by those employees that were purposely meant to use it. In view of that, the aim of this paper is to investigate factors that could influence employee’s intention to use e-collection system in the performance of their duties. Technology Acceptance Model (TAM) was adapted with an extension of computer self-efficacy variable with a view to providing additional explanation to the model. Partial Least Square (PLS) was used to analyse 116 responses from e-collection users in investigating the relationship between three independent variables (perceived usefulness, perceived ease of use, computer self-efficacy) and the dependent variable (intention). The results of the analysis revealed that positive and significant relationships exist between the independent variables and the dependent variable except between perceived usefulness and intention. Recommendations were made to the hospital authorities to educate and enlighten the concern employees on the usefulness and benefits of the new system.